2021
DOI: 10.1021/acs.est.1c04245
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Polyoxometalates that Achieve Efficient Wastewater Reclamation and Source Recovery via Forward Osmosis

Abstract: Forward osmosis (FO) has been increasingly used for water treatment. However, the lack of suitable draw solutes impedes its further development. Herein, we design pH-responsive polyoxometalates, that is, (NH4)6Mo7O24 and Na6Mo7O24, as draw solutes for simultaneous water reclamation and resource recovery from wastewater via FO. Both polyoxometalates have a cage-like configuration and release multiple ionic species in water. These characteristics allow them to generate high osmotic pressures to drive the FO sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…[20,24] After intercalation, two new peaks at 883 and 648 cm −1 emerged in [Mo 7 O 24 ] 6− -pCN, which were separately attributed to MoO and MO in [Mo 7 O 24 ] 6− polyanions. [25] These results definitely confirmed the existence of [Mo 7 O 24 ] 6− polyanions in g-C 3 N 4 . By comparing, it could be found that the peaks for CN at 806, 887, and 3167 cm −1 shifted to the higher wavenumbers (812, 891, and 3184 cm −1 , respectively) for [Mo 7 O 24 ] 6− -pCN.…”
Section: Characterizations Of Materialssupporting
confidence: 69%
“…[20,24] After intercalation, two new peaks at 883 and 648 cm −1 emerged in [Mo 7 O 24 ] 6− -pCN, which were separately attributed to MoO and MO in [Mo 7 O 24 ] 6− polyanions. [25] These results definitely confirmed the existence of [Mo 7 O 24 ] 6− polyanions in g-C 3 N 4 . By comparing, it could be found that the peaks for CN at 806, 887, and 3167 cm −1 shifted to the higher wavenumbers (812, 891, and 3184 cm −1 , respectively) for [Mo 7 O 24 ] 6− -pCN.…”
Section: Characterizations Of Materialssupporting
confidence: 69%
“…Likewise, [NH 4 ] 6 [Mo 7 O 24 ] is regenerated by pH regulation in the presence of ammonia. Thus, the regeneration of the POMs in this study is achieved in a one-step process without extra energy input and involving no toxic chemicals and organic solvents, which are extensively used in the recycling of draw solutes proposed elsewhere. , In addition, the recovered POMs show good repeatability in both their physicochemical properties and FO performance (Figure c,d), indicating that the POMs have excellent chemical stability as well as recyclability and reusability as draw solutes. This study demonstrates the superiority of POMs over commonly studied draw solutes and their potentials in antiviral-drug wastewater treatment, providing inspiration for future draw solute exploration.…”
Section: Resultsmentioning
confidence: 82%
“…The absorptions at 1550 and 1400 cm −1 are caused by the bending vibrations of O−H and N−H, respectively. 31,32 The absorption peaks at 920 and 870 cm −1 , which are only present in the MoO 3 raw material, are from the respective symmetric and asymmetric stretching vibrations of Mo�O. 33 With the Mo�O moiety being converted to Mo−O in POMs, the absorption of Mo�O disappears and an emerging peak at 663 cm −1 appears in POMs but is absent in MoO 3 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…The water affinity of responsive draw solutes undergoes reversible changes upon responding to external stimuli, such as electric and magnetic elds, gas, salt, pH, light, and temperature. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Table 1 presents the previous research on responsive draw solutes. The responsiveness of responsive draw solutes enables the facile separation of the draw solute aer the water permeation process, making them more attractive than non-responsive draw solutes.…”
Section: Introductionmentioning
confidence: 99%